Evaluating the conditions of family farming maize storage in Mahelane, Mozambique - Mulhanga, Arsénio Daniel Ivo; Rebocho, Dade; Garcia, Dionatas Alex; Jeque, Domingos Armando Soquir; Zevo, Ivan Natividade Júlio (Revista Agrogeoambiental, 2022)
The problems of storage of agricultural products are an object of permanent study. The objective of this work was to survey some stages of production, mainly storage, by interviewing producers in Mahelane, Namaacha district, in Mozambique. We conducted semi-structured interviews with 40 producers, selecting those who work with the District Services of Economic Activities - SDAE, in a total area of 44 ha of production of various crops, especially corn. Respondents were selected through a non-probabilistic sampling, the “snowball” technique. The parameters evaluated were: the interviewees’ characterization, mean grain moisture, number of weevils, grain mass, and primary post-harvest operations run by small producers. Women represent the largest percentage of labor in the maize production fields in the Mahelane area. The stored maize moisture rate ranges between 14.5 % and 16.4 %, and storage time is between 9 months and 12 months. The maize in Mahelane is mostly stored on the cob, 65 %, and with straw, 75 %. The interviewed producers have several problems regarding the post-harvest of maize, requiring technical assistance and training, especially the local population, who need guidance on the best way to store the grain and the seed.